Influence of the downwash airflow distribution characteristics of a plant protection UAV on spray deposit distribution. (April 2022) - Zhan, Yilong; Chen, Pengchao; Xu, Weicheng; Chen, Shengde; Han, Yifang; Lan, Yubin; Wang, Guobin
Abstract : During the aerial spraying of pesticides by plant protection UAVs (unmanned aerial vehicles), droplets are deposited below the aircraft under the influence of rotor airflow. The existence of a downwash airflow can improve the deposition of spray on target crops. However, during operation, variations in flight altitude and the gradual decrease in the payload of pesticide solution in the tank leads to changes in the flow field below the UAV which affects droplets distribution. In order to study this, the downwash airflow speed and droplet distributions below a UAV under different flight altitudes (1.5–3 m) and payloads (0-10 kg) were measured and analysed. The results indicated that the changes in operational parameters normally found during operation can change distribution of downwash airflow in all directions but particularly vertical and this can affect the distribution of spray below the UAV. Through correlation analysis, it was shown that the vertical component of airflow (downwash) had a significant positive correlation with spray deposition and penetration (P < 0.05, B = 0.082, B = 0.029), and a negative correlation with droplet deposition uniformity (coefficient of variation) and drift (P < 0.05, B = −3.818, B = −0.042). Thus, it can be seen that downwash is conducive to spray deposition and penetration, which can improve the droplet distribution uniformity and reduce drift. Thus, the influence mechanism of UAV airflow on droplet distribution was explored and shown to strongly influence have the quality of spraying by plant protection UAVs. Highlights: Wireless wind speed sensors used to test the downwash airflow UAV. Reduction in payload affects the downwash airflow of UAV. Downwash airflow of UAV in turn affects spray distribution. Vertical downwash airflow has a significant correlation with droplet distribution.